"Aesthetic regime" in urban entrepreneurialism: public art venues in Shanghai. Issue 2 (8th April 2019) - Zheng, Jane
Abstract : Purpose: The purpose of this paper is to understand urban sculpture venues that emerged in the recent decade and their connections to the on-going entrepreneurial urban policies and urban strategies in Shanghai. How does this phenomenon relate to Shanghai's urban policies? How does urban sculpture development reflect the nature and characteristics of the urban sculpture authority? Design/methodology/approach: Case study is the major research method used to achieve an in-depth understanding of the developmental processes, mechanisms and characteristics of urban sculpture projects. Three cases were selected and studied using purposeful sampling methods, including Duolun Road Sculpture Project (2002), the Shanghai International Sculpture Center (2006) and the Jing'an Sculpture Park (2009). Findings: A twofold main argument is established in this paper. Urban sculpture venues emerged as a new type of instrument to advance urban entrepreneurial policies; the use of this instrument, however, also involves politics in that art politically transforms the features and functions of open spaces in Shanghai. Originality/value: Although scholarly interest in exploring cultural development through urban planning in the Chinese context is evident, urban sculpture planning (termed as "urban sculpture" in the Chinese ideological context) in Chinese metropolitan cities, in particular, is an unexplored topic, and thus leaves a gap in the knowledge. This paper introduces a new conceptual model, i.e., "aesthetic regime, " to describe the role of the urban sculpture authority in the development of the urban sculpture scene. It looks at the artistic representation of artworks, design of the sculpture venues, functionality of the artworks and social mechanisms for the actualization of these projects. An evolutional trend of the three sites across the decade is concerned.